Clinical Implications of the Perception of Time in Attention Deficit Hyperactivity Disorder (ADHD): A Review - Ptacek, Radek; Weissenberger, Simon; Braaten, Ellen; Klicperova-Baker, Martina; Goetz, Michal; Raboch, Jiri; Vnukova, Martina; Stefano, George B (Medical science monitor, 2019)
Attention deficit hyperactivity disorder (ADHD) is a lifelong neurodevelopmental disorder that can affect many areas of the daily life of individuals and is associated with poor health outcomes and with debilitating deficits in executive function. Recently, increasing numbers of research studies have begun to investigate the associations between neural and behavioral manifestations of ADHD. This review summarizes recent research on the perception of time in ADHD and proposes that this symptom is a possible diagnostic characteristic. Controlled studies on time perception have compared individuals with ADHD with typically developing controls (TDCs) and have used methods that include the Zimbardo Time Perspective Inventory (ZTPI). Practical approaches to time perception and its evaluation have shown that individuals with ADHD have difficulties in time estimation and discrimination activities as well as having the feeling that time is passing by without them being able to complete tasks accurately and well. Although ADHD has been associated with neurologic abnormalities in the mesolimbic and dopaminergic systems, recent studies have found that when individuals with ADHD are treated medically, their perception of time tends to normalize. The relationship between ADHD and the perception of time requires greater attention. Further studies on time perception in ADHD with other abnormalities, including executive function, might be approaches that refine the classification and diagnosis of ADHD and should include studies on its varied presentation in different age groups.
Keywords: Attention Deficit Disorder with Hyperactivity; hyperkinetická porucha; Executive Function; lidé; exekutivní funkce; Humans; Time Perception; vnímání času